New and little-known species of the genus Lacon Laporte, 1838 (Coleoptera: Elateridae) of Afghanistan and adjacent countries - Prosvirov, Alexander S. (Zootaxa, 2016)
Two new species of the genus Lacon Laporte, 1838 are described: L. elegantissimus sp. nov. (Afghanistan, India) and L. kabakovi sp. nov. (Afghanistan). L. caeruleus Schimmel, 1998 is recorded for the first time in Afghanistan, presence of L. funebris (Solsky, 1881) in Afghanistan is confirmed. In addition, some taxonomic and morphological notes on the Lacon species of Afghanistan and adjacent countries are given.